La traduction de l’innovation dans l’espace urbain en Amérique du Nord - Laurence Gervais-Linon (Revue LISA)
A certain number of issues related to the effects of technological and economic innovation on urban sociology have arisen in the United States. The spatial concentration of innovation activities in the US and in Canada has created a “geography of innovation”. Technological, but also social, artistic and cultural innovations can have repercussions on urban space. What is called innovation may be hard to define but its symptoms are usually found in big urban centers and allow certain regions to stand out. This paper proposes to study three important aspects of the effects of economic innovation on urban space: firstly, urban decline and reinvestment processes linked to the gentrification of inner-cities; secondly, the role played by new social classes arising from the transformation of the economy; and lastly, the concept of metropolisation related to the concentration of tertiary activities.